Evaluation of the synapse adhesion molecule Kirrel3 in neurological disease - Shennib, Omar; Raines, Olivia; Karamian, Amanda Sandoval; Williams, Megan E. (Frontiers in Neurology, 2025)
The synaptic adhesion molecule KIRREL3 regulates synapse development in mice and is implicated in human neurological disorders, including autism spectrum disorder, intellectual disability, and Jacobsen syndrome (chromosome 11q deletion syndrome). However, its status as a definitive human disease gene remains unresolved, likely due to the rarity of KIRREL3-related disorders and significant gaps in understanding its molecular mechanisms. Current knowledge is further fragmented across disparate clinical and basic research reports, often buried in supplemental data. This review synthesizes existing evidence to enable clinicians and scientists to better evaluate KIRREL3 variants as potentially disease causing. We review its conserved role in mediating neuron-to-neuron interactions during axon targeting and synapse formation in mice and how disruptions to these interactions could contribute to neurological pathology in humans. We also discuss how disease-associated variants alter KIRREL3 function. Our analysis underscores the need for integrated studies spanning basic and clinical investigation to validate KIRREL3’s disease association and advance future interventions for KIRREL3-related disorders.